Compact MIMO antenna with high isolation characteristic for UWB portable applications. Issue 3 (13th November 2019) - Chang, Yujia; Liu, Qiang; Tang, Xianggan; Du, Guangxing; Li, Guolin; Cheng, Dong
Abstract: A compact two elements multiple‐input multiple‐output (MIMO) antenna is proposed. The simple monopoles act as the radiating elements, and the parasitic resonant elements near the monopoles make the antenna better matched in the low band. At back of the substrate, the ground planes of the elements are loaded by three curved branches for introducing additional resonant frequencies, which not only decreases the volume of the antenna but also increases the bandwidth. High isolation is achieved between the two antenna elements by adding three parallel metal strips on the back of the substrate. A MIMO antenna prototype with a compact size of 39 × 17.5 × 1 mm 3 is fabricated and measured. The measured and simulated results show that the band of the antenna covers 3.13 to 3.20 GHz and 7.87 to 12.08 GHz, and it can prevent the interference from the bands of WiMAX (3.4‐3.8 GHz) and C‐band (4‐7.87 GHz). The peak gain of the proposed antenna is 2.9 dBi, the envelope correlation coefficient and mutual coupling between the two elements are respectively lower than 0.001 and −20 dB in the band, Therefore, the antenna is very suitable for portable ultrawideband MIMO systems.